2018
DOI: 10.3390/colloids2020016
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Chemistry in Steam-Based Thermal Recovery of Oil Sands Bitumen with Emphasis on Steam-Assisted Gravity Drainage and the Role of Chemical Additives

Abstract: In this article, the importance of colloids and interfaces in thermal heavy oil or bitumen extraction methods is reviewed, with particular relevance to oil sands. It begins with a brief introduction to the chemical composition and surface chemistry of oil sands, as well as steam-based thermal recovery methods. This is followed by the specific consideration of steam-assisted gravity drainage (SAGD) from the perspective of the interfacial chemistry involved and factors responsible for the displacement of bitumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 137 publications
0
23
0
Order By: Relevance
“…Density‐driven convective flow is ubiquitous in natural systems, such as water infiltration into soil (Assouline, 2013), atmospheric movement (Hodges & Thorncroft, 1997) and oceanic currents (Ruddick & Gargett, 2003). Density‐driven convection has an wide application for flow in porous media, including geothermal energy production (Cheng & Minkowycz, 1977), oil separation from sand (Taylor, 2018), and carbon dioxide sequestration (Amooie et al, 2018; Mahmoodpour et al, 2019). It is well identified that when dense fluid sits above less dense fluid due to solute concentration and/or temperature, the system is easy to lose its equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…Density‐driven convective flow is ubiquitous in natural systems, such as water infiltration into soil (Assouline, 2013), atmospheric movement (Hodges & Thorncroft, 1997) and oceanic currents (Ruddick & Gargett, 2003). Density‐driven convection has an wide application for flow in porous media, including geothermal energy production (Cheng & Minkowycz, 1977), oil separation from sand (Taylor, 2018), and carbon dioxide sequestration (Amooie et al, 2018; Mahmoodpour et al, 2019). It is well identified that when dense fluid sits above less dense fluid due to solute concentration and/or temperature, the system is easy to lose its equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…All these methods of extraction are a special type of separation process used for heatsensitive materials like essential oils, resins, hydrocarbons, etc. which are insoluble in water and may decompose at their boiling point (Taylor, 2018). The temperature of the steam must be high enough to vaporize the essential oil present, yet not destroyed or burned the essential oils.…”
Section: Resultsmentioning
confidence: 99%
“…It is assumed that the water film is stabilized by electrostatic forces resulting from the formation of a double electric layer at the boundary of the phase separation of «oil -water» and «water -sand» [11][12][13][14].…”
Section: Methods Of Oil Sands Developmentmentioning
confidence: 99%